Primary Central Nervous System Angiitis Mimicking a Space-Occupying Lesion - Edmond Jonathan Gandham; Bimal Patel; Vivek Mathew; Krishna Prabhu Raju (Indian Journal of Neurosurgery, 2024)
Background and Purpose Intracranial space-occupying lesions are a sine qua non for neoplastic lesions; however, occasionally non-neoplastic lesions mimic neoplastic lesions, leading to diagnostic dilemmas. We report our experience with three patients who presented with a progressive hemispheric syndrome and the diagnostic considerations involved in the cases.